(untitled) (Nueva Epoca, 2020)
In the present work the antecedents of this «imported» institute are analyzed, where the Economic Analysis of Law plays an important role, in addition, alien to the country’s legal tradition. It is observed from the incorporation to the microsystem of the consumer defense law that in the Argentine doctrine and by re- flection in the jurisprudence, controversies have been generated in questions related to the denomination, functions, attribution factor, destination of the funds, areas of application among others. With the entry into force of the Civil and Commercial Code, the possibility of applying all damages is unleashed. In this state of affairs it is necessary to abandon positions and understand that solutions are found in the current Code, in constant dialogue with the national constitution and the protection microsystems.